Pengaruh Modal Teknologi Informasi Dan Komunikasi Terhadap Kinerja Inovasi - Setiadi, Pungki Andriani; Narsa, I Made (E-Jurnal Akuntansi; Vol 29 No 2 (2019)DO - 10.24843/EJA.2019.v29.i02.p18, 2019)
This study aims to investigate the relationship between Information and Communication Technologies (ICT) on innovation performance. Information and Communication Technologies consist of ICT Infrastructure, ICT Personnel, ICT Training, and ICT Department. This research method uses descriptive quantitative method with a questionnaire as a method of data acquisition. The subjects of this study were 70 respondents taken by random sampling method from various manufacturing companies in Surabaya. Data analysis techniques using Partial Least-Square (PLS). The results of this study indicate that ICT Infrastructure and ICT Training have a significant effect on innovation performance. Meanwhile, ICT Personnel and ICT Department did not significantly influence innovation performance. Keywords : ICT Infrastructure; ICT Personnel;  ICT Training; ICT Department; Innovation Performance.